Thyroid associated ophthalmopathy: evidence for CD4+ γδ T cells; de novo differentiation of RFD7+ macrophages, but not of RFD1+ dendritic cells; and loss of γδ and αβ T cell receptor expression. Issue 6 (17th May 2004) - Eckstein, A K; Quadbeck, B; Tews, S; Mann, K; Krüger, C; Mohr, C H; Steuhl, K-P; Esser, J; Gieseler, R K
Abstract : Aim: To characterise periorbital immune cells (stages, kinetics) in active and inactive thyroid associated ophthalmopathy (A-TAO; I-TAO). Methods: In orbital tissue cryosections of patients with A-TAO (n = 15), I-TAO (n = 11), and healthy controls (n = 14), adipose and fibrovascular areas were evaluated for MHC II + cells, CD45 + total leukocytes, myeloid cells (CD33 + monocytes; CD14 + macrophages; mature RFD7 + macrophages; RFD1 + dendritic cells (DCs)), and lymphoid cells (CD4 + T cells; αβ and γδ T cells; CD20 + B cells). Results are expressed as medians and 5% confidence intervals. Results: In fibrovascular septae, a surge of CD33 + immigrants clearly correlating with disease activity generated significantly increased (p<0.05) percentages of CD14 + and RFD7 + macrophages. Intriguingly, CD4 + cells were mostly γδ T cells, while αβ T helper cells were much less frequent. Successful treatment rendering TAO inactive apparently downregulates monocyte influx, macrophage differentiation, and T cell receptor expression. Similar trends were recorded for adipose tissue. Interestingly, RFD1 + DCs were completely absent from all conditions examined. Conclusion: A-TAO coincides with periorbital monocyte infiltration and de novo differentiation of macrophages, but not DCs. The authors discuss a novel potential role for inflammatory CD4 + γδ T cells in TAO. Successful treatment apparently downregulates orbital monocyte recruitment and effects functional T cell knockout.